2004
DOI: 10.1111/j.1365-2273.2004.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between change of hearing and (modified) Amsterdam Inventory for Auditory Disability and Handicap Score

Abstract: This study investigates the test-retest distributions and the interval for true score change of the (modified) Amsterdam Inventory for Auditory Disability and Handicap [(m)AIAD], when the latter is used to measure the effect of an intervention. In a previous study the reliability and validity of the (m)AIAD in a cohort of hearing impaired patients were found to have satisfactory high values. In this prospective study, 66 patients underwent a tympanoplasty operation. Preoperatively and postoperatively pure tone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
18
0
3
Order By: Relevance
“…This often causes depression, anxiety and social withdrawal [6]. This leads to a reduced health-related QOL in different dimensions (physical, functional, social, psychological, familial) [7,8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This often causes depression, anxiety and social withdrawal [6]. This leads to a reduced health-related QOL in different dimensions (physical, functional, social, psychological, familial) [7,8]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies were focused on the influence of reduced hearing on HR-QOL, but did not pay attention to the symptoms. These studies include validated instruments like the Hearing Handicap Inventory for Adults (HHIA) and the (modified) Amsterdam Inventory Auditory Disability and Handicap Score [6,8]. Measurements of all aspects of HR-QOL in patients with CSOM with validated measurement tools were, however, to date, only rarely carried out systematically [15].…”
Section: Discussionmentioning
confidence: 99%
“…For example, attempts were made to apply this questionnaire for measuring the effect of middle ear surgery with the aim of improving hearing, as well as for evaluation of the relation between the audiometric and psychometric measures of hearing after tympanoplasty (Meijer et al, 2004(Meijer et al, , 2006. The results of the latter investigation indicated that the (m)AIADH scores were almost independent of hearing loss for postoperative hearing levels in the range of 25-40 dB.…”
Section: Results Of Pta and Teoaementioning
confidence: 99%
“…The unsatisfactory evaluation of subjective QOL by patients with revision surgery and bilateral disease as compared to the primary surgery patients can possibly be explained by the prolonged course and associated higher burden of the disease, and absence of stereophonic hearing. 4,10 CONCLUSIONS: Tympanoplasty did lead to a significant improvement of disease-specific HR-QOL in patients with CSOM while general HR-QOL did not change. Very well correlations were found between 19 the subscale hearing function from the COMOT-15 questionnaire and Audiological findings.…”
Section: Discussionmentioning
confidence: 99%